2014
DOI: 10.2174/13816128113199990417
|View full text |Cite
|
Sign up to set email alerts
|

Gut Inflammation: Current Update on Pathophysiology, Molecular Mechanism and Pharmacological Treatment Modalities

Abstract: Inflammatory bowel disease (IBD) is a chronic and relapsing inflammatory condition of the gastrointestinal tract. The two main forms of IBD are Crohn's disease and ulcerative colitis. According to the recent concept the disease is caused by a combination of factors, including genetics, immune dysregulation, barrier dysfunction and the change in microbial flora. Environmental factors, such as changes in diet, antibiotic use, smoking or improved domestic hygiene (e.g. eradication of intestinal helminths) probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 328 publications
(370 reference statements)
1
31
0
Order By: Relevance
“…In the rest regions (f, c and g, inflammation related), for gut advantage transcripts, in region f, IFN-γ and IFN induced proteins implied Th1 response46; and the immunoglobulin heavy chain (μ and another one) transcripts suggested coexistence of IgM and probably IgT4748. In region c, proinflammatory factors (IL-1β and CCR6) and T cell markers (CD3 and CD8) indicated CTL responses occurred in the inflammatory gut49; and F-type lectin was in line with other reports of fish inflammation5051.…”
Section: Discussionmentioning
confidence: 99%
“…In the rest regions (f, c and g, inflammation related), for gut advantage transcripts, in region f, IFN-γ and IFN induced proteins implied Th1 response46; and the immunoglobulin heavy chain (μ and another one) transcripts suggested coexistence of IgM and probably IgT4748. In region c, proinflammatory factors (IL-1β and CCR6) and T cell markers (CD3 and CD8) indicated CTL responses occurred in the inflammatory gut49; and F-type lectin was in line with other reports of fish inflammation5051.…”
Section: Discussionmentioning
confidence: 99%
“…Their pathogenesis is complex, involving various predisposing environmental and genetic factors, which together with the altered intestinal flora can induce mucosal disruption and result in penetration of luminal antigens into the gut wall, followed by an ungoverned immune response and a chronic inflammatory reaction (Xavier and Podolsky, 2007;Gyires et al, 2014;Neurath, 2014). Numerous agents are available to treat IBD patients (Bryant et al, 2015), but many of them cause severe adverse reactions, or fail to maintain long-term remission, and a lot of effort is currently put into finding new therapeutic approaches (Gyires et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the Toll-like receptor-4 (TLR4) pathway is a major downstream signalling pathway for LPS. Notably, TLR4 is not only associated with microbial pathogenesis but also with multiple diseases such as IBD, autoimmune and allergic diseases [23-25]. Moreover, TLR4 is involved in the inflammation response, particularly in the secretion of inflammatory cytokines because it links several key inflammation-associated pathways such as NF-κB, MAPK and IRF3 [25-27].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, TLR4 is not only associated with microbial pathogenesis but also with multiple diseases such as IBD, autoimmune and allergic diseases [23-25]. Moreover, TLR4 is involved in the inflammation response, particularly in the secretion of inflammatory cytokines because it links several key inflammation-associated pathways such as NF-κB, MAPK and IRF3 [25-27]. As MIMP showed a significant inhibitory effect on LPS-induced inflammation, we hypothesized that MIMP may regulate inflammatory cytokines through affecting the TLR4 pathway.…”
Section: Resultsmentioning
confidence: 99%